"We just need the developer to develop": Entrepreneurialism, financialization and urban redevelopment in Lexington, Kentucky. (November 2021) - Ward, Kevin; Wood, Andrew
Since the 1980s US city governments have increased their use of more speculative means of financing economic redevelopment. This has involved experimenting with a variety of financial and taxation instruments as a way of growing their economies and redeveloping their built environments. This very general tendency, of course, masks how some cities have done well through the use of these instruments while others have not. The work to date has tended to pivot around a "winner-loser dichotomy", which emphasises either the capacity of US cities to be able to experiment and speculate through the use of one financial instrument or another or their failings with these instruments, resulting in bankruptcy and fiscal crisis. This paper presents a case study of Lexington, Kentucky and using archival research and interviews we argue that speculative financial instruments are harder to choreograph for some cities than for others. We draw particular attention to US cities beyond those that tend to be over-represented in the metro-centric academic literature. This argument has conceptual significance. Building theory out of the experiences of US cities such as Lexington, Kentucky turns attention to the work required by city governments as they seek to finance the redevelopment of their downtowns. We make the case for a continued appreciation of the messy politics around the use of financial instruments, and its indeterminate, open and unpredictable nature in an era of fragile and uncertain entrepreneurial US urban policy-making.